Fashion retailing - Diamond, Ellen (New York : Delmar, 1993)
This book is about: Introduction to fashion retailing; The fashion retailer's environment; Management and control functions; Communicating with and servicing the fashion clientele; ...
Keywords: Fashion merchandising; Fashion merchandising -- United States